Efficacy and safety of CYP2C19 genotype in stroke or transient ischemic attack patients treated with clopidogrel monotherapy or clopidogrel plus aspirin: Protocol for a systemic review and meta-analysis. Issue 24 (June 2018) - Yao, Jia-Chen; Cui, Min; Pan, Mang-Mang; Gu, Zhi-Chun; Li, Wen-Yan
Abstract: Background: The relationship of CYP2C19 genotype and clinical efficacy in stroke or transient ischemic attack (TIA) patients treated with clopidogrel monotherapy or clopidogrel plus aspirin remains unknown. We thus aim to conduct a meta-analysis to appraise evidence on the association of CYP2C19 genotype and clinical efficacy for stroke or TIA. Methods: An electronic search will be performed for clinical trials that reported the interested efficacy data (stroke, myocardial infarction, or vascular death) and safety data (any bleeding) in clopigogrel-treated patients with stroke or TIA. Odds ratios (ORs) with their confidence intervals (CIs) will be calculated using a meta-analysis. Results: This study will provide the evidence of the relationship between CYP2C19 genotype and clinical efficacy and safety in stroke/TIA patients taking clopidogrel by pooling the results of individual studies. Conclusions: The results will bring about vigorous evidence in this issue and guide both clinical decision-making and future research.